Recombinant hemagglutinin displaying on yeast reshapes congenital lymphocyte subsets to prompt optimized systemic immune protection against avian influenza infection - Zhang, Han; Li, Zexing; Zhang, Huixia; Guo, Yanyu; Zhang, Xinyi; Zhang, Lilin; Yang, Liu; Li, Shujun; Li, Changyan; Cui, Daqing; Xie, Ruyu; Li, Yongqing; et al. (Frontiers in Microbiology, 2023)
Prophylactic vaccination is regarded as the most effective means to control avian flu infection. The limited effectiveness, inconvenience administration routine requires a universal vaccine that provides broad and long-lasting protection against influenza. In the study, we generated a yeast surface displaying hemagglutinin (HA) H5, H7 and H9 of influenza virus. The protective efficacy was investigated in chickens after exposure to H9N2 influenza virus. Our results showed that oral yeast vaccine provided less clinical syndrome, reduced viral loading and alleviated airway damage significantly. Compared to the commercial inactivated vaccine, yeast vaccine stimulated the activation of spleenic NK and APCs cells, and boosted TLR7-IRF7-IFN signaling in spleen. Meanwhile, γδ T cells in the bursa of Fabricius are stimulated to activate，and the innate lymphoid cells (ILCs) in the bursa of Fabricius promoted the CILPs to differentiate to ILC3 cells in oral yeast birds. Moreover, the reshaped gut microbiota and a suppressed Th17-IL17-mediated inflammation in intestine was observed in oral yeast chickens, which might facilitate the recovery of intestinal mucosal immunity upon virus infection. Collectively, suggest that oral yeast based multivalent bird flu vaccines provide an attractive strategy to update host defense function via reshapes of multi-systemic immune homeostasis.